Fleksibilitas Peserta Didik SMA dan MA dalam Membentuk Identitas Budaya Daerah Setempat Sebagai Penduduk Pendatang di Kabupaten OKU Selatan - Fitri, Novita Aidil; Yosef, Yosef (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2025)
This study aims to determine the difference in flexibility in forming local cultural identity between SMA and MA students as migrant residents in South OKU Regency. This research uses a quantitative comparative approach. The sample consisted of 176 migrant students, namely 96 SMA students and 80 MA students from four schools: SMA Negeri 1 Muaradua, SMA Negeri 2 Muaradua, MA Negeri 1 OKU Selatan, and MA Negeri 2 OKU Selatan. The data were collected using a closed-ended questionnaire that had been tested for validity and reliability. The results of the t-test analysis show that there is a significant difference in the cultural identity flexibility between SMA and MA students. These findings indicate that the school environment affects the process of forming students' cultural identity.